Ambientalização vegetal na escola como abordagem prática no ensino de botânica - Silva, Jedson Raimundo Oliveira (2024)
This research, conducted at a school in the Rondônia State Network, located in Porto Velho, in the Amazon region, investigated the integration between popular and scientific knowledge about medicinal plants. The sequence of activities aimed to analyze the contributions of this approach to the development of an educational product aimed at teaching botany, to answer the question that drove the research: What are the contributions of a sequence of activities on medicinal plants, taking into account the development of an educational product to assist in teaching botany? The theoretical foundation, supported by several authors, promoted an approach that dialogues with traditional and scientific knowledge, emphasizing the importance of teaching Botany in the context of public educational policies. The methodological procedures used a qualitative and ethnobotanical approach, which involved a combination of methods used in botany, anthropology, history, ecology, among other disciplines, to understand how plants are used and valued in different cultures. Data collection was developed and carried out in the first half of 2023. The plan was aimed at students in the 2nd year of high school, at the Jorge Teixeira de Oliveira school in the city of Porto Velho. The analysis of the results showed that the students had prior knowledge about medicinal plants, based on their Amazonian reality, rich in medicinal species. The consumption of teas and infusions was highlighted as a common practice, arousing students' interest in research. During the meetings, students became protagonists, demonstrating motivation not only to achieve academic success, but also to develop practical skills and take on responsibilities. The research revealed that the participants' central doubt was the correct identification of medicinal plants and their appropriate use, highlighting the importance of correlating empirical knowledge with scientific knowledge. The interaction between theory and practice was considered crucial, highlighting the need for teaching closer to the students' reality, even without advanced resources. The study pointed to the need for changes in the didactic approach, promoting the integration between scientific and practical knowledge, providing meaningful learning. The research resulted in a booklet as an educational product, suggesting that the sequence of activities can bring substantial benefits to classes, aligning with the premises of educational quality. This approach aims to promote a deeper connection between academic learning and students' reality, establishing a meaningful and enriching bridge. The product was made available at the link: http://educapes.capes.gov.br/handle/capes/743439.